2016
DOI: 10.3748/wjg.v22.i3.933
|View full text |Cite
|
Sign up to set email alerts
|

Protective links between vitamin D, inflammatory bowel disease and colon cancer

Abstract: Vitamin D deficiency has been associated with a wide range of diseases and multiple forms of cancer including breast, colon, and prostate cancers. Relatively recent work has demonstrated vitamin D to be critical in immune function and therefore important in inflammatory diseases such as inflammatory bowel disease (IBD). Because vitamin D deficiency or insufficiency is increasingly prevalent around the world, with an estimated 30%-50% of children and adults at risk for vitamin D deficiency worldwide, it could h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(94 citation statements)
references
References 142 publications
0
79
0
11
Order By: Relevance
“…1,25D3 in the diet or delivered rectally decreased the severity and extent of inflammation in wild-type mice[35]. Furthermore, human studies documented some benefits of supplemental vitamin D in maintaining remission of Crohn’s disease[37]. However, the mechanism is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…1,25D3 in the diet or delivered rectally decreased the severity and extent of inflammation in wild-type mice[35]. Furthermore, human studies documented some benefits of supplemental vitamin D in maintaining remission of Crohn’s disease[37]. However, the mechanism is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…It regulates immune cells trafficking and differentiation, intestinal permeability, and antimicrobial peptide synthesis [98]. Several studies revealed an inverse association between serum concentration of 25-hydroxy-vitamin D and mucosal inflammation in IBD patients [105,106].…”
Section: Pharmaconutritionmentioning
confidence: 99%
“…Such examples are some amino acids like glutamine, arginine and tryptophan [96], omega-3 PUFA [97], vitamin D [98], and curcumin [99].…”
Section: Pharmaconutritionmentioning
confidence: 99%
“…A large number of preclinical studies have demonstrated several effects of vitamin D on the hallmarks of cancer, including anti-proliferative, anti-metastasis, anti-angiogenesis, pro-apoptosis and pro-differentiation activities891011121314. Observational studies have also revealed significant relationships of vitamin D with breast cancer, colorectal cancer, prostate cancer and pancreatic cancer610151617. Additionally, vitamin D deficiency could increase the risk of developing cancer and lead to a lower QOL1819.…”
mentioning
confidence: 99%